Transformation of Pancoran Village through Education Tourism and Green Environment Management for Sustainable Empowerment - Gumilang, Dendi Anggi (Journal of Sustainable Community Development (JSCD), 2025)
Community service in Pancoran RW 04 Village, South Jakarta, is carried out with an approach based on "Green Village" and "Eduwisata." This program aims to increase public knowledge, skills, and awareness of environmental conservation and encourage sustainable social and economic impacts. Several trainings were conducted, including photography and social media, digital marketing management, life skills education, and crop cultivation techniques on narrow plots. The results of the activity show that the community's ability to utilize digital technology for local promotion, independent environmental management, and increasing food security through hydroponic practices has increased. In addition, the Green House that was built functions as an environmental education center and community laboratory. The success of this program reflects the effectiveness of a participatory approach in empowering urban communities. This concept not only creates ecological change but also supports the social and economic sustainability of the community, which is relevant to be replicated in other regions.